Macroprudential Policy, Countercyclical Bank Capital Buffers, and Credit Supply: Evidence from the Spanish Dynamic Provisioning Experiments - Jiménez, Gabriel; Ongena, Steven; Peydró, José-Luis; Saurina, Jesús (Journal of Political Economy, 2017)
To study the impact of macroprudential policy on credit supply cycles and real effects, we analyze dynamic provisioning. Introduced in Spain in 2000, revised four times, and tested in its countercyclicality during the crisis, it affected banks differentially. We find that dynamic provisioning smooths credit supply cycles and, in bad times, supports firm performance. A 1 percentage point increase in capital buffers extends credit to firms by 9 percentage points, increasing firm employment (6 percentage points) and survival (1 percentage point). Moreover, there are important compositional effects in credit supply related to risk and regulatory arbitrage by nonregulated and regulated but less affected banks.